IICA action strategy in Jamaica: 1990-1991 - Instituto Interamericano de Cooperación para la Agricultura (IICA) (Instituto Interamericano de Cooperación para la Agricultura (IICA), 2020)
The document refers to the overall strategy for the 1990-1991 biennium: a) to assist the Government of Jamaica in bringing Jamaican back to its pre-Hurricane Gilbert level of development, while at the same time developing, testing and improving certain technologies and methodologies which result in: a) linking the small farmers to the export market, thereby improving their changes of increasing income; b) assisting small farmers to test and adapt appropriate technologies on their farms; c) providing simple record-keeping information and analysis which will assist the MOA and the small farmers to monitor farm income; d) encouraging youth to perceive agriculture as a serious and potentially lucrative vocation; e) providing policy-makers with projections and analyses of the impact of proposed agrarian policies; f) enabling the MOA to provide improved services in animal health and plant protection to the farmer and the country. Chapter 2 refers to agriculture in the country: a) overview of the social, economic, and political situation; b) summary of agricultural sector problems; and outlook for the sector and investment projects. Chapter 3 refers to possible areas for IICA actions. Chapter 4 refers to strategy for the period. Last, the utilization of assigned resources under negotiation: is dealt with human, financial, and plans for obtaining external resources. Four annexes are included: IDB 1988 Socio-Economic Report and Stermshorn trip report, among others.